LANDSLIDES, EARTHQUAKES, AND EROSION - Malamud B.D.; Turcotte D.L.; Guzzetti F.; Reichenbach P. (My University, 2004)
This paper relates landslide inventories to erosion rates and provides quantitative estimates of the landslide hazard associated with earthquakes. We do this by utilizing a three-parameter inverse-gamma distribution, which fits the frequency–area statistics of three substantially ‘complete’ landslide-event inventories. A consequence of this general distribution is that a landslide-event magnitude mL=logNLT can be introduced, where NLT is the total number of landslides associated with the landslide event. Using this general distribution, landslide-event magnitudes mL can be obtained from incomplete landslide inventories, and the total area and volume of associated landslides, as well as the area and volume of the maximum landslides, can be directly related to the landslide-event magnitude. Using estimated recurrence intervals for three landslide events and the time span for two historical inventories, we estimate regional erosion rates associated with landslides as typically 0.1–2.5 mm year−1. We next give an empirical correlation between the earthquake magnitude, associated landslide-event magnitude, and the total volume of associated landslides. Using these correlations, we estimate that the minimum earthquake magnitudes that will generate landslides is M=4.3±0.4. Finally, using Gutenberg–Richter frequency-magnitude statistics for regional seismicity, we relate the intensity of seismicity in an area and the magnitude of the largest regional earthquakes to erosion rates. We find that typical seismically induced erosion rates in active subduction zones are 0.2–7 mm year−1 and adjacent to plate boundary strike-slip fault zones are 0.01–0.7 mm year−1.